Multidrug-resistant Staphylococcus cohnii and Staphylococcus urealyticus isolates from German dairy farms exhibit resistance to beta-lactam antibiotics and divergent penicillin-binding proteins - Tobias Lienen (Nature Portfolio, 2021)
Abstract Non-aureus staphylococci are commonly found on dairy farms. Two rarely investigated species are Staphylococcus (S.) cohnii and S. urealyticus. Since multidrug-resistant S. cohnii and S. urealyticus are known, they may serve as an antimicrobial resistance (AMR) gene reservoir for harmful staphylococcal species. In our study, nine S. cohnii and six S. urealyticus isolates from German dairy farms were analyzed by whole-genome sequencing and AMR testing. The isolates harbored various AMR genes (aadD1, str, mecA, dfrC/K, tetK/L, ermC, lnuA, fexA, fusF, fosB6, qacG/H) and exhibited non-wildtype phenotypes (resistances) against chloramphenicol, clindamycin, erythromycin, fusidic acid, rifampicin, streptomycin, tetracycline, tiamulin and trimethoprim. Although 14/15 isolates lacked the blaZ, mecA and mecC genes, they showed reduced susceptibility to a number of beta-lactam antibiotics including cefoxitin (MIC 4–8 mg/L) and penicillin (MIC 0.25–0.5 mg/L). The specificity of cefoxitin susceptibility testing for mecA or mecC gene prediction in S. cohnii and S. urealyticus seems to be low. A comparison with penicillin-binding protein (PBP) amino acid sequences of S. aureus showed identities of only 70–80% with regard to PBP1, PBP2 and PBP3. In conclusion, S. cohnii and S. urealyticus from selected German dairy farms show multiple resistances to antimicrobial substances and may carry unknown antimicrobial resistance determinants.